Can cultural tourism experience enhance cultural confidence? The evidence from Qingyuan Mountain - Lin, Jian; Kang, Yanxin; Hong, Liping; Huang, Yijun (Frontiers in Psychology, 2022)
A questionnaire survey was conducted among 600 visitors to the region using Qingyuan Mountain, a 5A picturesque location in Quanzhou City, Fujian Province, as the research site. A total of 489 valid questionnaires were received. The links between cultural involvement, cultural experience, cultural identity, cultural confidence, and cultural loyalty were experimentally examined using a structural equation modelling technique. The results showed that cultural experience was a mediating factor in the processes of the influence of cultural involvement on cultural identity and the influence of cultural involvement on cultural confidence, but the influence of cultural involvement on cultural identity and the influence of cultural involvement on cultural confidence were not supported. The study accordingly condenses theoretical contributions to academia and management insights for businesses.